Ab-Initio Computational Study : The Activation Energy Changes and Steric Effects In Peptide Synthesis Of Ac-AA-NH2 and Ac-AP-NH2 - Pratiwi, Indah; Cahyono, Bambang; Siahaan, Parsaoran (Universitas Jenderal Soedirman, 2021)
Ab-Initio computational method can be used for simulating reaction mechanisms, such as concerted reaction mechanism on peptide synthesis. The concerted reaction is one of many possible pathways on how peptide can be synthesized. The purpose of this study are probing the concerted reaction mechanism and comparing the steric effect to the reaction, given by different side-chain of alanine (A) and proline (P). Two dipeptides formed from alanine and proline were computed at HF-SCF/6-31G** theory level: Ac-AA-NH2 and Ac-AP-NH2. The res.lts show the activation energy of Ac-AA-NH2 and Ac-AP-NH2 forming via concerted pathway are 167.541 kJ/mol and 161.044 kJ/mol, respectively. The steric difference in side-chain affects the dihedral angle of the structure, and also gives difference to the entropy value of reaction.